Memorundum of Understanding (MOU) between International Water Management Institute (IWMI) and Water Management Authority (WARMA) Zambia - International Water Management Institute; Water Management Authority (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
IWMI and WARMA (Water Management Authority, Zambia) formaliZed their collaboration through the signing of an MOU. The purpose of the MOU is to establish a framework for collaboration between WARMA and IWMI. The two institutions agreed to establish and operationalize early warning systems for drought and floods in Zambia.